Photocurable adhesive composition, cured product, connection structure, and method for producing connection structure
A photocurable adhesive composition with a thermal acid generator and onium salt structure addresses the issue of fading in high-temperature, high-humidity environments by maintaining light-shielding and adhesive properties through acid generation in these conditions.
Patent Information
- Application Number
- JP2023093886
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-07
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2043-06-07
AI Technical Summary
Photocurable adhesive compositions used in high-temperature, high-humidity environments lose their light-shielding properties over time due to the fading of leuco dyes, as they rely on photoacid generators that are activated by UV rays, which are absorbed by pigments, preventing deep penetration and incomplete curing.
Incorporating a thermal acid generator with an onium salt structure into the photocurable adhesive composition, which generates acid in high-temperature, high-humidity conditions to maintain light-shielding properties by supplying acid to leuco dyes, ensuring complete curing and color development.
The composition maintains effective light-shielding properties and adhesive strength in high-temperature, high-humidity environments by using a thermal acid generator to counteract fading, ensuring durability and functionality.
Smart Images

Figure 2024175842000001_ABST
Abstract
Description
[Technical field]
[0001] The present technology relates to a photocurable adhesive composition, a cured product, a connection structure, and a method for producing a connection structure. [Background technology]
[0002] A representative method for imparting light-shielding properties to a cured resin is to add a pigment such as carbon black to color the resin in advance. However, in the case of a photocurable adhesive composition (ultraviolet-curable resin composition), if the resin composition is colored in advance, ultraviolet light is absorbed by the pigment and the ultraviolet light does not reach the depths of the resin composition sufficiently, which may cause the resin composition to remain uncured deep inside.
[0003] Therefore, a method can be exemplified in which a leuco dye (e.g., a leuco dye) and a photoacid generator are added to an ultraviolet-curable resin composition, which is colorless before ultraviolet irradiation, but is colored by generating an acid from the photoacid generator upon ultraviolet irradiation, and the generated acid is added to the leuco dye. In this method, it is important to shift the timing of curing and coloring of the resin composition in order to achieve both ultraviolet curability and light-shielding properties.
[0004] For example, Patent Document 1 describes a method for curing a photocurable resin composition, which is characterized by a step of sequentially irradiating a photocurable resin composition containing a leuco dye, a photoacid generator, a radical polymerizable compound, and a radical initiator with a plurality of active energy rays having different wavelengths. Specifically, in the method described in Patent Document 1, the photocurable resin composition is first irradiated with an active energy ray having a wavelength of 400 nm or more to generate radicals from the photoradical generator, and then irradiated with an active energy ray having a wavelength of 370 nm or less to generate an acid from the photoacid generator, thereby achieving both high light blocking properties and thick film curing properties.
[0005] However, the cured product of the photocurable resin composition described in Patent Document 1 fades in a high-temperature and high-humidity environment, and the light-shielding property is lost over time. That is, the photocurable resin composition described in Patent Document 1 has difficulty in maintaining the light-shielding property in a high-temperature and high-humidity environment after curing. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. WO2016 / 129568 Summary of the Invention [Problem to be solved by the invention]
[0007] The present technology has been proposed in view of the above-mentioned conventional circumstances, and provides a photocurable adhesive composition that can maintain light-shielding properties even in a high-temperature and high-humidity environment after curing. [Means for solving the problem]
[0008] The photocurable adhesive composition according to the present technology contains (a) a photocurable radical polymerization component, (b) a photoradical generator, (c) a photoacid generator, (d) a leuco dye, and (e) a thermal acid generator having an onium salt structure.
[0009] The cured product according to the present technology is obtained by curing a photocurable adhesive composition that contains (a) a photocurable radical polymerization component, (b) a photoradical generator, (c) a photoacid generator, (d) a leuco dye, and (e) a thermal acid generator having an onium salt structure.
[0010] The connection structure according to the present technology is formed by connecting via a cured product of the above-mentioned photocurable adhesive composition.
[0011] A method for manufacturing a connection structure according to the present technology includes a step of irradiating the above-mentioned photocurable adhesive composition disposed between a first component and a second component with light to cure the photocurable adhesive composition. Effect of the Invention
[0012] The present technology can provide a photocurable adhesive composition that can maintain its light-blocking properties even in a high-temperature and high-humidity environment after curing. [Brief description of the drawings]
[0013] [Figure 1] FIG. 1 is a cross-sectional view showing a lens module that is an example of a connection structure according to the present technology. [Diagram 2] FIG. 2 is a cross-sectional view for explaining an example of step A of the manufacturing method of the lens module. [Diagram 3] FIG. 3 is a cross-sectional view for explaining an example of step B of the manufacturing method of the lens module. [Figure 4] FIG. 4 shows members used when measuring the adhesive strength of the cured photocurable adhesive composition, where FIG. 4(A) is a perspective view of an LCP and FIG. 4(B) is a perspective view of a PC. [Diagram 5] FIG. 5 is an oblique view illustrating a method for measuring the adhesive strength of a cured photocurable adhesive composition. FIG. 5(A) is an oblique view illustrating an example of a method for placing a PC and an LCP on a jig and applying a photocurable adhesive composition between the PC and the LCP. FIG. 5(B) is an oblique view illustrating an example of a method for irradiating the photocurable adhesive composition with UV. FIG. 5(C) is an oblique view illustrating an example of a connection structure in which a PC and an LCP are connected with a cured product of the photocurable adhesive composition. FIG. 5(D) is a side view illustrating an example of a connection structure in which a PC and an LCP are connected with a cured product of the photocurable adhesive composition. FIG. 5(E) is an oblique view illustrating a method for measuring the adhesive strength of the cured product of the photocurable adhesive composition in the connection structure. [Figure 6] FIG. 6 is a perspective view illustrating a method for evaluating the curability of a photocurable adhesive composition. FIGS. 6(A) and 6(B) are perspective views illustrating an example of a method for filling a space between LCPs with a photocurable adhesive composition. FIG. 6(C) is a perspective view illustrating an example of a method for curing the photocurable adhesive composition. FIG. 6(D) is a perspective view illustrating a method for measuring the length of the cured portion of the cured product in the UV irradiation direction in a connection structure connected with a cured product of the photocurable adhesive composition. [Figure 7]FIG. 7 is an oblique view illustrating a method for evaluating the light-blocking properties of a cured photocurable adhesive composition. FIGS. 7(A) and (B) are oblique views illustrating a method for applying a photocurable adhesive composition onto one piece of glass, placing the other piece of glass on the applied photocurable adhesive composition, and crushing the photocurable adhesive composition with the thickness of a spacer. FIG. 7(C) is an oblique view illustrating a method for curing the photocurable adhesive composition to obtain a connection structure in which two pieces of glass are connected by a cured product of the photocurable adhesive composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0014] <Photocurable adhesive composition> The photocurable adhesive composition according to the present technology contains (a) a photocurable radical polymerization component (hereinafter also referred to as “component (a)”), (b) a photoradical generator (hereinafter also referred to as “component (b)”), (c) a photoacid generator (hereinafter also referred to as “component (c)”), (d) a leuco dye (hereinafter also referred to as “component (d)”), and (e) a thermal acid generator having an onium salt structure (hereinafter also referred to as “component (e)”).
[0015] The photocurable adhesive composition comprising the components (a) to (d) undergoes a curing reaction of the photocurable radical polymerization component by light irradiation, and also undergoes a reaction in which an acid is generated from the photoacid generator by light irradiation, and the generated acid is added to the leuco dye, thereby changing the photocurable adhesive composition from colorless to colored, thereby imparting light-shielding properties. Thus, the photocurable adhesive composition according to the present technology undergoes a curing reaction and a light-shielding reaction by light irradiation. However, the photocurable adhesive composition comprising the components (a) to (d) fades in a high-temperature and high-humidity environment after curing, and therefore loses its light-shielding properties over time.
[0016] Therefore, the photocurable adhesive composition according to the present technology further contains (e) a thermal acid generator having an onium salt structure in addition to the components (a) to (d), so that after curing, an acid is generated from the thermal acid generator in a high-temperature, high-humidity environment, and the generated acid is supplied to the leuco dye, thereby suppressing fading of the leuco dye in a high-temperature, high-humidity environment. Therefore, the photocurable adhesive composition according to the present technology can maintain light-shielding properties even in a high-temperature, high-humidity environment after curing.
[0017] Here, a high temperature and high humidity environment refers to an environment with a temperature and humidity such that the leuco dye in the cured product of the photocurable adhesive composition fades, for example, 85° C. and a relative humidity of 85%.
[0018] In addition, the photocurable adhesive composition according to the present technology has good light-shielding properties after curing. That is, the cured product of the photocurable adhesive composition according to the present technology also has good light-shielding properties before being placed in a high-temperature, high-humidity environment. Furthermore, the photocurable adhesive composition according to the present technology has good curability and adhesive strength after curing. Therefore, the photocurable adhesive composition according to the present technology can be preferably applied to a connection structure in which a first member and a second member are connected via a cured product of the photocurable adhesive composition according to the present technology. When the photocurable adhesive composition according to the present technology is used to connect members in a lens module (camera module), for example, the initial adhesive strength required for the lens module can be improved, and the adhesive strength after being placed in a high-temperature, high-humidity environment can also be maintained.
[0019] In addition, in the technology described in the above-mentioned Patent Document 1, in order to achieve both high light-shielding properties and thick-film curing properties, a step of sequentially irradiating with multiple active energy rays with different wavelengths is an essential condition. In contrast, the photocurable adhesive composition according to the present technology has good curing properties and good light-shielding properties after curing even when irradiated with light of a single wavelength (e.g., ultraviolet light with a wavelength of 365 nm) alone.
[0020] <(a) Photocurable radical polymerization component> The photocurable radical polymerization component is a compound containing a radical polymerizable group. From the viewpoint of improving the adhesive strength after curing and improving the curability of the photocurable adhesive composition, the component (a) is preferably a compound containing a (meth)acryloyl group. The (meth)acryloyl group includes both a methacryloyl group and an acryloyl group. The component (a) may be a monomer, an oligomer, or a combination of a monomer and an oligomer, but from the viewpoint of improving the adhesive strength of the photocurable adhesive composition after curing and improving the curability of the photocurable adhesive composition, a combination of an oligomer (photocurable oligomer) and a monomer (photocurable monomer) is preferred.
[0021] <(a1) Photocurable oligomer> The photocurable oligomer (hereinafter also referred to as "(a1) component") may be monofunctional, bifunctional, or polyfunctional, but from the viewpoint of improving the adhesive strength of the photocurable adhesive composition after curing and from the viewpoint of improving the curability of the photocurable adhesive composition, a bifunctional photocurable oligomer or a polyfunctional photocurable oligomer is preferred. As the (a1) photocurable oligomer, for example, a urethane (meth)acrylate oligomer can be used, and specifically, a urethane (meth)acrylate oligomer having a polybutadiene skeleton, a urethane (meth)acrylate oligomer having a polycarbonate skeleton, a urethane (meth)acrylate oligomer having a polyether skeleton, a urethane (meth)acrylate oligomer having a polyester skeleton, an isoprene-based (meth)acrylate oligomer, etc. can be used. Among these, from the viewpoint of the adhesive strength and curability of the photocurable adhesive composition after curing, a urethane (meth)acrylate having a polyester skeleton is preferred. An example of a commercially available photocurable oligomer that can be used is UV-3200B (manufactured by Mitsubishi Chemical Corporation). The photocurable oligomer may be used alone or in combination of two or more kinds.
[0022] <(a2) Photocurable monomer> The photocurable monomer (hereinafter also referred to as "component (a2)") may be monofunctional, bifunctional, or polyfunctional. For example, a monofunctional monomer having a ring structure (specifically, an alicyclic structure, a heterocyclic structure, an aromatic ring structure, etc.) can be used. The component (a2) may be used alone or in combination of two or more. From the viewpoint of improving the light-shielding properties of the photocurable adhesive composition, improving the adhesive strength of the photocurable adhesive composition after curing, and improving the curability of the photocurable adhesive composition, it is preferable that the photocurable monomer (a2) contains an acrylamide-based monomer, and it is also preferable to use an acrylamide-based monomer in combination with a monomer having an aromatic ring structure, or to use an acrylamide-based monomer in combination with a monomer having an alicyclic structure.
[0023] Examples of acrylamide monomers include (meth)acrylamide, dimethyl(meth)acrylamide, diethyl(meth)acrylamide, (meth)acryloylmorpholine, hydroxyethyl(meth)acrylamide, isopropyl(meth)acrylamide, dimethylaminopropyl(meth)acrylamide, (meth)acrylamide, Nt-butyl(meth)acrylamide, N-methylol(meth)acrylamide, N-methoxymethyl(meth)acrylamide, N-butoxymethyl(meth)acrylamide, and diacetone(meth)acrylamide.
[0024] Examples of monomers having an aromatic ring structure include benzyl (meth)acrylate, phenyl (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxypolyethylene glycol (meth)acrylate, nonylphenoxypolyethylene glycol (meth)acrylate, phenoxypolypropylene glycol (meth)acrylate, 2-(meth)acryloyloxyethyl-2-hydroxypropyl phthalate, and 2-hydroxy-3-phenoxypropyl (meth)acrylate.
[0025] Examples of monomers having an alicyclic structure include isobornyl (meth)acrylate, dicyclopentanyl (meth)acrylate, dicyclopentenyl (meth)acrylate, dicyclopentenyloxy (meth)acrylate, dicyclopentenyloxyethyl acrylate, adamantyl (meth)acrylate, 2-alkyl-2-adamantyl (meth)acrylate, 3-hydroxy-1-adamantyl (meth)acrylate, and 1-perfluoroadamantyl (meth)acrylate.
[0026] In particular, the component (a2) preferably contains acryloylmorpholine, and it is also preferable to use acryloylmorpholine and isobornyl acrylate in combination, or acryloylmorpholine and benzyl acrylate in combination.
[0027] The total content of the component (a) in the photocurable adhesive composition is preferably 90% by mass or more from the viewpoint of improving the adhesive strength of the cured photocurable adhesive composition and the curability of the photocurable adhesive composition. The upper limit of the total content of the component (a) in the photocurable adhesive composition is not particularly limited and may be, for example, 96% by mass or less or 94% by mass or less.
[0028] When the (a) component includes the (a1) component and the (a2) component, the content of the (a1) component relative to the total amount of the (a) component is preferably 10% by mass or more, may be 15% by mass or more, may be 20% by mass or more, may be 10 to 60% by mass, may be 10 to 50% by mass, may be 10 to 40% by mass, or may be 40 to 60% by mass. The content of the (a2) component relative to the total amount of the (a) component is preferably 20% by mass or more, may be 30% by mass or more, may be 40% by mass or more, may be 50% by mass or more, may be 60% by mass or more, may be 40 to 95% by mass, may be 20 to 80% by mass, may be 40 to 80% by mass, may be 40 to 75% by mass, or may be 40 to 70% by mass. When two or more (a) components are used in combination, it is preferable that the total amount thereof satisfies the above range. When the component (a) includes the components (a1) and (a2), the content of the component (a1) relative to the total amount of the photocurable adhesive composition is preferably 9 to 71 mass%, may be 9 to 54 mass%, may be 9 to 45 mass%, may be 35 to 54 mass%, or may be 35 to 45 mass%. When the component (a) includes the components (a1) and (a2), the content of the component (a2) relative to the total amount of the photocurable adhesive composition is preferably 18 to 91 mass%, may be 36 to 91 mass%, may be 36 to 80 mass%, or may be 50 to 91 mass%.
[0029] <(b) Photoradical generator> The photoradical generator is a photopolymerization initiator that generates radicals by irradiation with light. From the viewpoint of improving the adhesive strength of the photocurable adhesive composition after curing and the viewpoint of improving the curability of the photocurable adhesive composition, the component (b) is preferably, for example, an alkylphenone-based photopolymerization initiator or an acylphosphine oxide-based photopolymerization initiator. Specific examples of the component (b) include 1-hydroxycyclohexyl phenyl ketone and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide. Commercially available products of the component (b) include, for example, PI-184 (manufactured by Aal Chem) and Omnirad 819 (manufactured by IGM resins BV). The component (b) may be used alone or in combination of two or more types.
[0030] The content of the (b) component may be 0.1 parts by mass or more, or may be 0.5 parts by mass or more, or may be 1 part by mass or more, when the total amount of the (a) component is 100 parts by mass, from the viewpoint of improving the adhesive strength of the cured photocurable adhesive composition and the viewpoint of improving the curability of the photocurable adhesive composition. The upper limit of the content of the (b) component may be 15 parts by mass or less, or may be 10 parts by mass or less, or may be 5 parts by mass or less, when the total amount of the (a) component is 100 parts by mass, from the viewpoint of improving the adhesive strength of the cured photocurable adhesive composition and the viewpoint of improving the curability of the photocurable adhesive composition. When two or more (b) components are used in combination, it is preferable that the total amount thereof satisfies the above range.
[0031] <(c) Photoacid generator> The photoacid generator is a compound that generates an acid such as a Lewis acid or a Bronsted acid upon irradiation with light. The acid generated from the component (c) is added to the leuco dye, thereby changing the photocurable adhesive composition from colorless to colored, and imparting light-shielding properties to the photocurable adhesive composition.
[0032] From the viewpoint of improving the curability of the photocurable adhesive composition, it is preferable that the component (c) does not absorb too much light at a wavelength of 365 nm, and for example, an iodonium salt-based photoacid generator or a sulfonium salt-based photoacid generator is preferable. In addition, the component (c) contains a hexafluorophosphate anion ([PF 6 ] - ), [PR 1 6 ] - or an anion represented by [BR 2 4 ] - It is preferable that the anion contains an anion represented by [PR 1 6 ] - For the anion represented by R 1 each independently represents a fluorine atom or a fluorinated alkyl group, and at least one R 1 is a fluorinated alkyl group. 1 6 ] - An example of an anion represented by the formula [PF 3 (C 2 F 5 ) 3 ] - [BR 2 4 ] - For the anion represented by R 2 each independently represents a fluorine atom or a fluorinated alkyl group having 1 to 4 carbon atoms, and at least one R 2 is a fluorinated alkyl group. 2 4 ] - An example of the anion represented by the formula: is tetrakis(hexafluorophenyl)borate anion.
[0033] Specific examples of the component (c) include an iodonium salt-based photoacid generator containing a hexafluorophosphate anion, a sulfonium salt-based photoacid generator containing a hexafluorophosphate anion, and [PF 3 (C 2 F 5 ) 3 ]- Examples of the photoacid generator include a sulfonium salt-based photoacid generator containing a tetrakis(hexafluorophenyl)borate anion, a sulfonium salt-based photoacid generator containing a tetrakis(hexafluorophenyl)borate anion, and an iodonium salt-based photoacid generator containing a tetrakis(hexafluorophenyl)borate anion.
[0034] From the viewpoint of the curability of the photocurable adhesive composition, preferred are iodonium salt-based photoacid generators containing tetrakis(hexafluorophenyl)borate anion, iodonium salt-based photoacid generators containing hexafluorophosphate anion, sulfonium salt-based photoacid generators containing hexafluorophosphate anion, and sulfonium salt-based photoacid generators containing tetrakis(hexafluorophenyl)borate anion, which have relatively low light absorption at a wavelength of 365 nm, and more preferred are iodonium salt-based photoacid generators containing tetrakis(hexafluorophenyl)borate anion, iodonium salt-based photoacid generators containing hexafluorophosphate anion, and sulfonium salt-based photoacid generators containing hexafluorophosphate anion.
[0035] Commercially available products of component (c) include PI-2074 (manufactured by Arkema), WPI-170 (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.), AT-6992 (manufactured by Tomoe Engineering Co., Ltd.), CPI-310B (manufactured by San-Apro Ltd.), and CPI-410S (manufactured by San-Apro Ltd.) The component (c) may be used alone or in combination of two or more kinds.
[0036] The content of the (c) component may be 0.1 parts by mass or more, 0.5 parts by mass or more, or 1 part by mass or more, when the total amount of the (a) component is taken as 100 parts by mass, from the viewpoint of improving the light-shielding property of the photocurable adhesive composition after curing. The upper limit of the content of the (c) component may be 20 parts by mass or less, 10 parts by mass or less, 5 parts by mass or less, or 3 parts by mass or less, when the total amount of the (d) component is taken as 100 parts by mass, from the viewpoint of curability. For example, the content of the (c) component is preferably in the range of 0.5 to 6 parts by mass, when the total amount of the (a) component is taken as 100 parts by mass, from the viewpoint of improving the light-shielding property of the photocurable adhesive composition after curing and the curability of the photocurable adhesive composition. The content of the (c) component may be in the range of 100 to 600 parts by mass, when the total amount of the (d) component is taken as 100 parts by mass, from the viewpoint of improving the curability of the photocurable adhesive composition. When two or more types of (c) components are used in combination, it is preferable that the total amount thereof falls within the above range.
[0037] <(d) Leuco dye> The leuco dye is a compound that develops color upon contact with an acid, and is a component for imparting light-shielding properties to the cured product of the photocurable adhesive composition. From the viewpoint of the light-shielding properties of the photocurable adhesive composition, the component (d) is preferably a leuco dye, and more preferably a leuco dye that develops a black color. A specific example of the component (d) is (2'-anilino-6'-dibutylamino-3'-methylspiro[phthalido-3,9'-[9H]xanthene]). A commercially available product of the component (d) is BLACK 400 (manufactured by Yamada Chemical Industry Co., Ltd.). The component (d) may be used alone or in combination of two or more types.
[0038] For example, when BLACK 400 represented by the following formula 1 is used as component (d), after curing, the photocurable adhesive composition according to the present technology generates an acid from component (e) in a high-temperature, high-humidity environment. When the generated acid is supplied to component (d), the lactone ring in component (d) opens as shown in formula 2, and component (d) changes from colorless to colored (black) and develops color. This imparts light-blocking properties to the photocurable adhesive composition, making it possible to suppress fading of component (d) in a high-temperature, high-humidity environment.
[0039] formula 1 [ka]
[0040] formula 2 [ka]
[0041] The content of the (d) component in the photocurable adhesive composition is preferably 0.2% by mass or more, may be 0.5% by mass or more, may be 0.8% by mass or more, or may be 1% by mass or more, from the viewpoint of improving the light-shielding property of the photocurable adhesive composition after curing. The upper limit of the content of the (d) component in the photocurable adhesive composition is not particularly limited, and may be, for example, 5% by mass or less, 3% by mass or less, 2% by mass or less, or 1.5% by mass or less. When two or more kinds of (d) components are used in combination, it is preferable that the total amount thereof satisfies the above range.
[0042] <(e) Thermal acid generator having an onium salt structure> The thermal acid generator is a compound that generates an acid in a high-temperature, high-humidity environment and suppresses discoloration of the component (d) in the cured product of the photocurable adhesive composition. From the viewpoint of maintaining the light-shielding properties of the cured photocurable adhesive composition in a high-temperature, high-humidity environment and improving the adhesive strength of the cured photocurable adhesive composition, the component (e) is preferably a thermal acid generator having an onium salt structure, and more preferably a thermal acid generator having a quaternary ammonium salt structure or a thermal acid generator having a sulfonium salt structure. The component (e) preferably has a tetrakis(hexafluorophenyl)borate anion or a CF 3 SO 3 - Specific examples of the component (e) include a photoacid generator containing a tetrakis(hexafluorophenyl)borate anion and a quaternary ammonium salt structure, CF 3 SO 3 -and a photoacid generator containing a quaternary ammonium salt structure. Commercially available products of the component (e) include CXC-1821, CXC-1614 (both manufactured by Kusumoto Chemicals Co., Ltd.), and TA-100 (manufactured by San-Apro Co., Ltd.). The component (e) may be used alone or in combination of two or more kinds.
[0043] From the viewpoint of maintaining the light-shielding properties of the cured product of the photocurable adhesive composition under high temperature and high humidity conditions, and from the viewpoint of improving the adhesive strength after curing, the content of the (e) component is preferably 0.1 mass% or more, may be 0.5 mass% or more, or may be 0.75 mass% or more, based on the total content of the (d) component. The upper limit of the content of the (e) component is not particularly limited, and may be, for example, 3 mass% or less, may be 2 mass% or less, or may be 1.5 mass% or less, based on the total content of the (d) component. When two or more (e) components are used in combination, it is preferable that the total amount thereof satisfies the above range.
[0044] <Other ingredients> The photocurable adhesive composition may further contain other components in addition to the components (a) to (e) as long as the effects of the present technology are not impaired. Examples of the other components include an acid trapping agent, a filler, a solvent, and a sensitizer.
[0045] From the viewpoint of curability, the photocurable adhesive composition preferably does not substantially contain a sensitizer, and the content of the sensitizer in the photocurable adhesive composition is more preferably 0.5 mass % or less, further preferably 0.4 mass % or less, and particularly preferably 0.1 mass % or less. Since the photocurable adhesive composition does not substantially contain a sensitizer, the irradiated light is not absorbed by the sensitizer, and therefore deterioration of the curability of the photocurable adhesive composition can be prevented.
[0046] <Cured Product of Photocurable Adhesive Composition> The cured product of the photocurable adhesive composition according to the present technology is obtained by curing the photocurable adhesive composition containing the above-mentioned components (a) to (e). Hereinafter, the cured product of the photocurable adhesive composition according to the present technology will also be simply referred to as the "cured product according to the present technology". In the cured product according to the present technology, acid is generated from component (e) in a high-temperature, high-humidity environment, and the generated acid is supplied to component (d), thereby suppressing discoloration of component (d) in a high-temperature, high-humidity environment. Therefore, the cured product according to the present technology can maintain light-shielding properties even in a high-temperature, high-humidity environment. That is, the cured product according to the present technology has good light-shielding properties before and after being placed in a high-temperature, high-humidity environment.
[0047] Regarding good light-shielding properties, since the wavelength at which the human eye is most sensitive is light at a wavelength of 550 nm, for example, the cured product according to the present technology has a transmittance of 25% or less at a wavelength of 550 nm when the product has a thickness of 200 μm before being placed in a high-temperature, high-humidity environment, and more preferably has a transmittance of less than 10% at a wavelength of 550 nm. Thus, the cured product according to the present technology has a transmittance of 25% or less at a wavelength of 550 nm, so that the light-shielding properties are good. In addition, the cured product according to the present technology has an increase in transmittance at a wavelength of 550 nm after being placed in a high-temperature, high-humidity environment (for example, an environment of 85° C. and relative humidity of 85%) for 72 hours, preferably 5% or less compared to the initial transmittance (before being placed in a high-temperature, high-humidity environment). The transmittance of the cured product according to the present technology can be measured by the method described in the Examples below.
[0048] In addition, the cured product according to the present technology has good adhesive strength, and can maintain good adhesive strength even after being placed in a high-temperature, high-humidity environment. That is, the cured product according to the present technology has good adhesive strength before and after being placed in a high-temperature, high-humidity environment. The adhesive strength of the cured product according to the present technology can be measured by the method described in the examples below.
[0049] <Connection structure> In the connection structure according to the present technology, a first member and a second member are connected via the above-mentioned cured product according to the present technology. FIG. 1 is a cross-sectional view showing a lens module 1, which is an example of the connection structure according to the present technology. The lens module 1 includes, for example, a flexible substrate 2 (FPC: Flexible Printed Circuits), a circuit board 3, an image sensor 4, a lens 5, a lens barrel 6, a housing 7, a sensor frame 8, and an IR cut filter 9. In the lens module 1, the focal length between the lens 5 and the image sensor 4 arranged on the circuit board 3 is fixed by the cured products 14d and 14e of the adhesive. Hereinafter, the lens 5, the lens barrel 6, and the housing 7 are collectively referred to as an optical unit 11. The flexible substrate 2, the circuit board 3, and the image sensor 4 are collectively referred to as a sensor unit 12. The lens barrel 6 and the housing 7 are collectively referred to as a lens housing 13.
[0050] Examples of the first member and the second member constituting the connection structure according to the present technology include the circuit board 3, the lens barrel 6, the housing 7, and the sensor frame 8 in the lens module 1 shown in FIG.
[0051] Examples of the flexible substrate 2 include a glass substrate and a plastic substrate. The flexible substrate 2 has a terminal for connecting to the circuit substrate 3. The flexible substrate 2 may have a single-layer structure or a multi-layer structure.
[0052] The circuit board 3 is a board on which the image sensor 4, the sensor frame 8, etc. are mounted. Wiring for transmitting signals from the image sensor 4, etc. is arranged on the circuit board 3. The circuit board 3 is formed, for example, of a printed circuit board (PCB). The circuit board 3 has terminals for connecting to the flexible board 2, and is connected to the terminals of the flexible board 2 via a cured product of the photocurable adhesive composition.
[0053] The image sensor 4 receives the light collected by the lens and converts it into an electrical signal. The image sensor 4 is composed of, for example, a charge coupled device (CCD) or a complementary metal oxide semiconductor (CMOS). The image sensor 4 is disposed on the circuit board 3. The image sensor 4 is connected to a pad formed on the circuit board 3 by, for example, a bonding wire. This pad is connected to the wiring of the circuit board 3.
[0054] The lens 5 is for collecting light from a subject. The lens 5 is attached to the lens barrel 6 at a predetermined position in order to converge the light (image) on the light receiving surface of the image sensor 4. The lens 5 includes a plurality of optical elements arranged along the lens barrel 6. For example, as shown in FIG. 1, the lens 5 is fixed to the lens barrel 6 by a cured product 14a of a photocurable adhesive composition. The lens 5 may be made of, for example, glass, plastic, or the like.
[0055] The lens barrel 6 is a lens tube for holding the lens 5, and is configured, for example, in a cylindrical shape. The lens barrel 6 is fixed to the housing 7 by a cured product 14b of the photocurable adhesive composition. From the viewpoint of moldability, the material of the lens barrel 6 may be, for example, an engineering plastic such as LCP (liquid crystal polymer) or polycarbonate.
[0056] The housing 7 is a case for holding the lens barrel 6. From the viewpoint of moldability, examples of the material of the housing 7 include engineering plastics such as LCP (liquid crystal polymer) and polycarbonate. The housing 7 is fixed to the lens barrel 6 by a cured product 14b of the photocurable adhesive composition, and is also fixed to the sensor frame 8 by a cured product 14d of the photocurable adhesive composition.
[0057] The sensor frame 8 is fixed to the housing 7 by a cured product 14d of the photocurable adhesive composition, and is also fixed to the circuit board 3 by a cured product 14e of the photocurable adhesive composition.
[0058] The IR cut filter 9 is a filter that has a function of transmitting visible light contained in the light that has passed through the lens 5 and cutting infrared light. The IR cut filter 9 is disposed between the sensor frame 8 and the lens 5. The IR cut filter 9 is fixed to the sensor frame 8 by a cured product 14c of the photocurable adhesive composition.
[0059] In the lens module 1 , incident light from the outside passes through the lens 5 and the IR cut filter 9 in this order, and then reaches the image sensor 4 .
[0060] All of the cured products 14a to 14e of the photocurable adhesive composition shown in FIG. 1 may be the cured products according to the present technology, or at least one of the cured products 14a to 14e of the photocurable adhesive composition may be the cured product according to the present technology. The cured product according to the present technology may be preferably used as the cured product 14b of the photocurable adhesive composition in the lens module 1 shown in FIG. 1. In addition, that is, an example of the connection structure according to the present technology is a lens module 1 in which a housing 7 as a first member and a lens barrel 6 as a second member are connected via a cured product 14b of the photocurable adhesive composition as a cured product according to the present technology. In the connection structure according to the present technology, the first member and the second member are connected via the cured product according to the present technology, so that the cured product can maintain light-shielding properties even when placed in a high-temperature and high-humidity environment. In addition, in the connection structure according to the present technology, the first member and the second member are connected via the cured product according to the present technology, so that the adhesive strength is good and the adhesive strength can be maintained even when placed in a high-temperature and high-humidity environment.
[0061] <Method of Manufacturing Connection Structure> The method for manufacturing a connection structure according to the present technology includes a step of irradiating a photocurable adhesive composition disposed between a first member and a second member with light to cure the photocurable adhesive composition.
[0062] The first member and the second member are synonymous with the first member and the second member in the connection structure described above.
[0063] The light irradiation conditions can be appropriately selected depending on the application of the photocurable adhesive composition according to the present technology. For example, a UV-LED with a wavelength of 365 nm is used as a light source, and the illuminance is 300 to 800 mW / cm. 2 The irradiation time can be set to 3 to 20 seconds.
[0064] A manufacturing method of the lens module 1, which is an example of a manufacturing method of the connection structure according to the present technology, includes the following steps A, B, and C.
[0065] 2 is a cross-sectional view for explaining an example of step A of the manufacturing method of the lens module. For example, in step A, a photocurable adhesive composition is applied between the circuit board 3 on which the image sensor 4 is mounted and the sensor frame 8, and / or between the sensor frame 8 and the optical unit 11 including the lens 5 and the lens housing 13. For example, as shown in FIG. 2, step A includes at least one of applying a photocurable adhesive composition 10e to the surface of the circuit board 3 on which the image sensor 4 is mounted and applying a photocurable adhesive composition 10d to the surface of the sensor frame 8 arranged on the circuit board 3 on which the image sensor 4 is mounted.
[0066] In addition, when the circuit board 3 on which the image sensor 4 is mounted and the sensor frame 8 are fixed in advance, only the photocurable adhesive composition 10d may be applied in the step A. In addition, for example, when the circuit board 3 on which the image sensor 4 is mounted and the sensor frame 8 are not fixed in advance, both the photocurable adhesive compositions 10d and 10e may be applied in the step A. In addition, for example, when the sensor frame 8 and the optical unit 11 are fixed in advance, only the photocurable adhesive composition 10e may be applied in the step A. In addition, when the lens barrel 6 and the housing 7 are not fixed in advance, the photocurable adhesive composition 10b may also be applied in the step A. In this way, all of the photocurable adhesive compositions 10a to 10e shown in FIG. 2 may be the photocurable adhesive composition according to the present technology described above, or at least one of the photocurable adhesive compositions 10a to 10e may be the photocurable adhesive composition according to the present technology.
[0067] The method for applying the photocurable adhesive compositions 10a to 10e is not particularly limited, and examples thereof include roll coating, doctor knife, die coating, dip coating, bar coating, inkjet, and jet dispensing.
[0068] 3 is a cross-sectional view for explaining an example of step B of the manufacturing method of the lens module. In step B, a connection structure 15 is formed, which includes a circuit board 3 on which an image sensor 8 is mounted, a sensor frame 8, and an optical unit 11, and in which the lens 5 and the image sensor 4 are focused. For example, in step B, the optical unit 11 is disposed on a photocurable adhesive composition 10d, and a connection structure 15 is formed in which the lens 5 constituting the optical unit 11 and the image sensor 4 are focused. In this way, in step B, the lens 5 and the image sensor 4 are aligned.
[0069] In step B, the optical axis of the optical unit 11 is adjusted. The adjustment of the optical axis of the optical axis unit 11 can be performed, for example, by displacing the optical unit 11 using an active alignment method. The adjustment of the optical axis of the optical unit 11 includes, for example, adjustments in the x-, y-, and z-axes and adjustment of the rotation angle.
[0070] In step C, the photocurable adhesive compositions 10a-10e in the connection structure 15 are irradiated with light to cure the photocurable adhesive compositions 10a-10e. Thus, in step C, the connection structure 15 formed in step B is fixed in the correct position, that is, with the lens 5 and the image sensor 4 in focus. By such a manufacturing method, the lens module 1 shown in FIG. 1 is obtained. EXAMPLES
[0071] Examples of the present technology will be described below. Note that the present technology is not limited to these examples. The components used in the examples and comparative examples are as follows.
[0072] <(a) Photocurable radical polymerization component> UV-3200B: Urethane acrylate oligomer, manufactured by Mitsubishi Chemical Corporation IBXA: Isobornyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd. #160: Benzyl acrylate, manufactured by Osaka Organic Chemical Industry Co., Ltd. ACMO: acryloylmorpholine, KJ Chemicals
[0073] <(b) Photoradical generator> PI-184: 1-hydroxycyclohexyl phenyl ketone, Aal Chem Omnirad 819: Phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide, IGM resins BV
[0074] <(c) Photoacid generator> PI-2074: Iodonium salt / tetrakis(hexafluorophenyl)borate anion, Arkema WPI-170: Iodonium salt / [PF 6 ] - , Fujifilm Wako Pure Chemical Industries, Ltd. AT-6992: Sulfonium salt / [PF 6 ] - , manufactured by Tomoe Engineering Co., Ltd. CPI-310B: Sulfonium salt / tetrakis(hexafluorophenyl)borate anion, San-Apro Co., Ltd. CPI-410S: Sulfonium salt / [PF 3 (C 2 F 5 ) 3 ] - , San-Apro Co., Ltd.
[0075] <(d) Leuco dye> BLACK 400: Yamada Chemical Industry Co., Ltd. (compound represented by the above formula 1)
[0076] <(e) Thermal acid generator> CXC-1821: Quaternary ammonium salt / tetrakis(hexafluorophenyl)borate anion, manufactured by Kusumoto Chemicals Co., Ltd. CXC-1614: Quaternary ammonium salt / CF 3 SO 3 - , manufactured by Kusumoto Chemicals NACURE 2500: Amine salt / tosylic acid, manufactured by Kusumoto Chemicals Co., Ltd. NACURE 5225: Amine salt / DDBSA (dodecylbenzenesulfonic acid), manufactured by Kusumoto Chemicals TA-100: Sulfonium salt / [PF 3 (C 2 F 5 ) 3 ] - , San-Apro Co., Ltd.
[0077] <Other ingredients> San-Aid SI-S: Acid trap, manufactured by Sanshin Scientific Co., Ltd. R974: Fumed silica, manufactured by Aerosil Solvent: Propylene carbonate, Fujifilm Wako Pure Chemical Industries, Ltd. KAYAKCURE DETX: Sensitizer, manufactured by Nippon Kayaku Co., Ltd.
[0078] <Preparation of Photocurable Adhesive Composition> The photocurable adhesive compositions of Experimental Examples 1 to 28 were prepared by uniformly mixing the components shown in Table 1 in the blending ratios (parts by mass) shown in Table 1. The photocurable adhesive composition of Experimental Example 2 not containing a thermal acid generator, the photocurable adhesive composition of Experimental Example 17 not containing a photoacid generator, and the photocurable adhesive composition of Experimental Example 24 not containing a leuco dye are comparative examples.
[0079] <Adhesive strength after curing> FIG. 4 shows members used in measuring the adhesive strength of the cured photocurable adhesive composition, where FIG. 4(A) is a perspective view of LCP21, and FIG. 4(B) is a perspective view of PC20 (Panlite L-1225Y, manufactured by Teijin). FIG. 5 is a perspective view for explaining a method for measuring the adhesive strength of the cured photocurable adhesive composition. First, as shown in FIG. 5(A), PC20 and LCP21 whose surface was plasma-treated were placed on a jig 22, and the photocurable adhesive composition 23 of Experimental Examples 1 to 28 was applied between PC20 and LCP21. The plasma treatment was performed using a plasma treatment device (manufactured by SAMCO, plasma cleaner: PC-300) under the conditions of treatment mode: Reactive Ion Edging, 125 W x 5 min x 2 cycles. Next, as shown in FIG. 5(B), a UV-LED (wavelength 365 nm) was used to measure the adhesive strength of the cured photocurable adhesive composition at an illuminance of 800 mW / cm. 2 The photocurable adhesive composition 23 was irradiated with UV for 20 seconds at 400° C. to cure the photocurable adhesive composition 23, thereby obtaining a connection structure 25 (see FIGS. 5(C) and (D)) in which the PC 20 and the LCP 21 were connected by a cured product 24 of the photocurable adhesive composition. FIG. 5(C) is a perspective view showing an example of the connection structure 25, and FIG. 5(D) is a side view showing an example of the connection structure 25.
[0080] FIG. 5(E) is a perspective view for explaining a method of measuring the adhesive strength of the cured product 24 of the photocurable adhesive composition in the connection structure 25. As shown in FIG. 5(E), from the PC20 side of the connection structure 25, using a measuring device (manufactured by Nippon Measurement Systems Co., Ltd., load tester: JSV H1000), in compression mode, it was pushed at 200 μm / sec until the connection structure came off, and the maximum value (peak strength) at that time was measured. Five test pieces (connection structures 25) were measured, and the average value was taken as the value of the Push strength (adhesive strength). The results are shown in Table 1. When the Push strength exceeded 4.5 MPa, it was evaluated as ◎, when it was 0.5 MPa or more and 4.5 MPa or less, it was evaluated as 〇, and when it was less than 0.5 MPa, it was evaluated as ×. Practically, it is preferable that the Push strength is 0.5 MPa or more, and more preferably more than 4.5 MPa.
[0081] <Adhesive strength after HTHH> The connection structure 25 shown in FIGS. 5(C) and (D) was placed in an environment of 85° C. and 85% relative humidity for 72 hours, and then, as shown in FIG. 5(E), from the PC20 side of the connection structure 25, using a measuring device (manufactured by Nippon Measurement Systems Co., Ltd., load tester: JSV H1000), in compression mode, it was pushed at 200 μm / sec until the connection structure came off, and the maximum value (peak strength) at that time was measured. Five test pieces (connection structures 25) were measured, and the average value was taken as the value of the Push strength (adhesive strength). The results are shown in Table 1. When the Push strength after HTHH exceeded 4.5 MPa, it was evaluated as ◎, when it was 0.5 MPa or more and 4.5 MPa or less, it was evaluated as 〇, and when it was less than 0.5 MPa, it was evaluated as ×. Practically, it is preferable that the Push strength after HTHH is 0.5 MPa or more, and more preferably more than 4.5 MPa.
[0082] <Curability> Fig. 6 is a perspective view for explaining a method for evaluating the curability of a photocurable adhesive composition. As shown in Fig. 6(A), two LCPs 26 and 27 (LAPEROS E525T, manufactured by Polyplastics Co., Ltd., flat plate: 20 mm x 50 mm x 2 mmt) were arranged so that the gap between them was 50 µm, and as shown in Fig. 6(B), the photocurable adhesive composition 28 of Experimental Examples 1 to 28 was filled between the LCPs 26 and 27. As shown in Fig. 6(C), a UV-LED (wavelength 365 nm) was used to apply an illuminance of 300 mW / cm2. 2 The photocurable adhesive composition 28 was irradiated with UV light for 3 seconds in the filling direction (vertical direction) of the photocurable adhesive composition 28 to cure the photocurable adhesive composition 28, thereby obtaining a connection structure 30 in which the two LCPs 26, 27 were connected by a cured product 29 of the photocurable adhesive composition.
[0083] As shown in FIG. 6(D), the length L of the cured portion of the cured product 29 in the UV irradiation direction in the surface direction of the LCP 26 was measured with an optical microscope (manufactured by Keyence Corporation). Specifically, the uncured portion of the cured product 29 was wiped with a rag or cotton swab, and the length L of the remaining cured portion was measured. The results are shown in Table 1. When the length of the cured portion of the cured product 29 was more than 0.9 mm, it was evaluated as ◎, when it was 0.45 mm or more and 0.9 mm or less, it was evaluated as ◯, and when it was less than 0.45 mm, it was evaluated as ×. For practical purposes, it is preferable that the length of the cured portion of the cured product 29 is 0.45 mm or more, and more preferably more than 0.9 mm.
[0084] <Light blocking property> 7 is a perspective view for explaining a method for evaluating the light-shielding property of the cured photocurable adhesive composition. As shown in Fig. 7(A) and (B), the photocurable adhesive composition 33 of Experimental Examples 1 to 28 was applied onto one piece of glass 31, the other piece of glass 32 was placed on the applied photocurable adhesive composition 33, and the photocurable adhesive composition 33 was compressed to the thickness (200 µm) of the spacer 34. As shown in Fig. 7(C), a UV-LED (wavelength 365 nm) was used to measure the light-shielding property of the cured photocurable adhesive composition at an illuminance of 1000 mW / cm2. 2The photocurable adhesive composition 33 was irradiated with UV for 4 seconds to cure the photocurable adhesive composition 33, and a connection structure 36 in which two pieces of glass 31 and 32 were connected by a cured product of the photocurable adhesive composition was obtained. For the cured product 35 in the obtained connection structure 36, the transmittance (initial transmittance) at a wavelength of 550 nm was measured. As the measuring device, UH4150 (UV-Vis spectrophotometer, manufactured by Hitachi High-Technologies Corporation) was used. An integrating sphere was used for the measurement. The results are shown in Table 1. When the transmittance of the cured product 35 at a wavelength of 550 nm was less than 15%, it was evaluated as ◎, when the transmittance was 15% or more and 25% or less, it was evaluated as 〇, and when the transmittance exceeded 25%, it was evaluated as ×. Practically, the transmittance of the cured product 35 at a wavelength of 550 nm is preferably 25% or less, and more preferably less than 15%.
[0085] <Light-shielding property after HTHH> After the connection structure 36 was placed in an environment of 85 °C and 85% relative humidity for 72 hours, as shown in Fig. 7(C), the transmittance at a wavelength of 550 nm when the thickness of the cured product 35 was 200 mm was measured. The results are shown in Table 1. With respect to the initial transmittance, when the increase in the transmittance of the cured product 35 at a wavelength of 550 nm after HTHH was 5% or less, it was evaluated as 〇, and when the increase in the transmittance exceeded 5%, it was evaluated as ×. Practically, the increase in the transmittance of the cured product 35 at a wavelength of 550 nm after HTHH is preferably 5% or less with respect to the initial transmittance.
[0086]
Table 1
[0087] From the results of Experimental Examples 1 to 28, it was found that the photocurable adhesive compositions used in Experimental Examples 1, 3, 4, 9 to 16, 18 to 23, and 25 to 28 had good light-shielding properties after HTHH because they contained (a) a photocurable radical polymerization component, (b) a photoradical generator, (c) a photoacid generator, (d) a leuco dye, and (e) a thermal acid generator having an onium salt structure. In other words, it was found that the cured products of the photocurable adhesive compositions used in these Experimental Examples were able to maintain their light-shielding properties even in high-temperature and high-humidity environments.
[0088] It was also found that the cured products of the photocurable adhesive compositions used in Experimental Examples 1, 3, 4, 9, 10, 11, 13 to 16, 18 to 22, and 25 to 28 were capable of maintaining light-shielding properties even in high-temperature and high-humidity environments, and also had good adhesive strength and curability. If the curability of the photocurable adhesive composition is insufficient, as in Experimental Examples 12 and 23, the curability can be improved by adjusting the wavelength and intensity of the light irradiation from the light source, the amount of (b) the photoradical generator, or the like, as necessary.
[0089] It was found that the photocurable adhesive compositions used in Experimental Examples 1, 3, 4, and 9 had good light-shielding properties after curing because they contained a predetermined amount or more of (e) a thermal acid generator having an onium salt structure. On the other hand, it was found that the light-shielding properties after HTHH were not good in Experimental Example 2, which used a photocurable adhesive composition that did not contain (e) a thermal acid generator having an onium salt structure. It was also found that the light-shielding properties after HTHH were not good in Experimental Examples 5 to 8, which used a thermal acid generator that did not have an onium salt structure.
[0090] From the results of Experimental Examples 1 and 10, it was found that a photocurable adhesive composition containing (a) a photocurable radical polymerization component, (b) a photoradical generator, (c) a photoacid generator, (d) a leuco dye, and (e) a thermal acid generator having an onium salt structure, can maintain its light-shielding properties even in a high-temperature and high-humidity environment after curing, and has good adhesive strength and curability after curing, regardless of the presence or absence of an acid trapping agent.
[0091] From the results of Experimental Examples 12 to 16, it was found that (a) a photocurable adhesive composition containing a predetermined amount of an oligomer as a photocurable radical polymerization component has better adhesive strength and curability after curing. Specifically, from the results of Experimental Examples 13 to 16, it was found that (a) a photocurable adhesive composition containing 9 to 54 mass% of an oligomer as a photocurable radical polymerization component has good curability. In addition, from the results of Experimental Examples 14 and 15, it was found that (a) a photocurable adhesive composition containing 35 to 45 mass% of an oligomer as a photocurable radical polymerization component has better adhesive strength and curability after curing.
[0092] The results of Experimental Examples 17 to 19 show that the cured product of the photocurable adhesive composition containing a predetermined amount or more of (c) a photoacid generator not only has good light-blocking properties after HTHH but also has good light-blocking properties before HTHH. On the other hand, the results of Experimental Example 17 show that the cured product of the photocurable adhesive composition not containing (c) a photoacid generator does not have good light-blocking properties before HTHH.
[0093] The results of Experimental Examples 20 to 23 show that a photocurable adhesive composition containing a photoacid generator (c) that has a relatively small absorption at a wavelength of 365 nm has better curability.
[0094] From the results of Experimental Examples 24 to 26, it was found that the cured product of the photocurable adhesive composition containing a predetermined amount or more of (d) leuco dye has better light-shielding properties. Specifically, from the viewpoint of light-shielding properties, it was found that a photocurable adhesive composition containing 0.2 mass % or more of (d) leuco dye is preferable, and a photocurable adhesive composition containing 0.9 mass % or more of (d) leuco dye is more preferable. On the other hand, from the results of Experimental Example 24, it was found that the cured product of the photocurable adhesive composition not containing (d) leuco dye has poor light-shielding properties both before HTHH and after HTHH.
[0095] The results of Experimental Examples 1 and 27 show that a photocurable adhesive composition containing (a) a photocurable radical polymerization component, (b) a photoradical generator, (c) a photoacid generator, (d) a leuco dye, and (e) a thermal acid generator having an onium salt structure, which does not contain a sensitizer, has better curability and adhesive strength after curing.
[0096] From the results of Experimental Examples 1 and 28, it was found that the photocurable adhesive composition containing (a) a photocurable radical polymerization component, (b) a photoradical generator, (c) a photoacid generator, (d) a leuco dye, and (e) a thermal acid generator having an onium salt structure was better in curability and adhesive strength after curing when irradiated with light of a single wavelength of 365 nm than when irradiated with light from a mercury-xenon lamp, when compared with light from a mercury-xenon lamp. This is thought to be because the light irradiated from a mercury-xenon lamp contains light of various wavelengths, and therefore it is more difficult to cure the photocurable adhesive composition to the inside than light of a single wavelength of 365 nm. [Explanation of symbols]
[0097] 1 Lens module, 2 Flexible board, 3 Circuit board, 4 image sensors, 5 lenses, 6 Lens barrel, 7 Housing, 8 Sensor Frame, 9 IR cut filter, 10a~10e Photocurable adhesive composition, 11 Optical unit, 12 sensor units, 13 Lens housing, 14a to 14e Cured products of photocurable adhesive compositions; 15 Connection structure, 20 pcs, 21 LCP, 22 Jigs, 23 Photocurable adhesive composition, 24 A cured product of a photocurable adhesive composition, 25 Connection structure, 26 LCP, 27 LCP, 28 Photocurable adhesive composition, 29 A cured product of a photocurable adhesive composition, 30 Connection structure, 31 Glass, 32 Glass, 33 Photocurable adhesive composition, 34 spacer, 35 Cured product of photocurable adhesive composition, 36 Connection structure
Claims
1. (a) a photocurable radical polymerization component; (b) a photoradical generator; and (c) a photoacid generator; and (d) a leuco dye; and (e) a thermal acid generator having an onium salt structure.
2. 2. The photocurable adhesive composition according to claim 1, wherein the content of the thermal acid generator (e) is 0.1 mass % or more based on the total amount of the leuco dye (d).
3. 3. The photocurable adhesive composition according to claim 1, wherein the content of the leuco dye (d) is 0.2 mass % or more.
4. 3. The photocurable adhesive composition according to claim 1, wherein the total content of the photocurable radical polymerization components (a) is 90 mass % or more.
5. 3. The photocurable adhesive composition according to claim 1, which has a transmittance of 25% or less at a wavelength of 550 nm after curing when the composition has a thickness of 200 μm.
6. The photocurable adhesive composition according to claim 1 or 2, which undergoes a curing reaction and a light-shielding reaction upon irradiation with light.
7. (a) a photocurable radical polymerization component; (b) a photoradical generator; and (c) a photoacid generator; and (d) a leuco dye; and (e) A cured product obtained by curing a photocurable adhesive composition containing a thermal acid generator having an onium salt structure.
8. The cured product according to claim 7, which has a transmittance of 25% or less at a wavelength of 550 nm when the product has a thickness of 200 μm.
9. 9. The cured product according to claim 7, which has a thickness of 200 μm and exhibits an increase in transmittance at a wavelength of 550 nm of 5% or less relative to the initial transmittance after being placed in an environment of 85° C. and a relative humidity of 85% for 72 hours.
10. A connection structure in which a first member and a second member are connected via a cured product of the photocurable adhesive composition according to claim 1 or 2.
11. 3. A method for producing a connection structure, comprising a step of irradiating the photocurable adhesive composition according to claim 1 or 2, which is disposed between a first member and a second member, with light to cure the photocurable adhesive composition.
Citation Information
Patent Citations
Photocurable resin composition suppressing short circuit between adjacent electrodes
JP2016147990A
Liquid resin composition for active ray-curable adhesive
JP2019196493A
Method for manufacturing adhesive sheet-attached article
JP2022046283A
Color-changeable adhesive sheet
JP2022046421A
Color-changeable adhesive sheet
JP2022046422A
